Validity and Reliability of Physical Fitness Test of Nusantara Students at SMP Padang City - Hasibuan, Yurmianna Marlina; Aziz, Ishak; Arsil, Arsil; Pranoto, Nuridin Widya; Barlian, Eri; Zarya, Fiky; Roy, Tendy (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The validity and reliability of the Nusantara Student Fitness Test instrument remain uncertain, prompting this study to investigate its efficacy. This research aims to assess the validity of various components of the test, including Body Mass Index (BMI), V Sit and Reach, 60-second Sit Up, Squat Thrust, Pacer Test, and overall reliability of the Nusantara Student Fitness Test (TKPN) instrument. A descriptive research method was employed, involving 109 junior high school students from Padang City across 11 districts. The sample comprised 143 students actively participating in extracurricular sports from SMP N 18 Padang City and SMP Adabiah Padang City. Data analysis utilized correlation tests (rxy) at a significance level of 0.05. The findings reveal several key outcomes: (1) BMI provided insights into students' nutritional status, with the majority exhibiting good nutrition; (2) The V Sit and Reach test exhibited validity (0.314 > 0.163), albeit not particularly useful; (3) The Sit Up test demonstrated acceptable validity (0.647 > 0.163); (4) The Squat Thrust test showed clear relevance (0.444 > 0.163); (5) The Pacer Test displayed very good validity (0.814 > 0.163); (6) The TKPN instrument exhibited medium reliability (0.676). These findings contribute to a better understanding of the Nusantara Student Fitness Test instrument's effectiveness and underscore the importance of validity and reliability assessments in fitness evaluation tools.